Peningkatan Hasil Belajar Bercakap Cakap dalam Bahasa Inggris menggunakan Media Puzzle pada Siswa Kelas V SD YPPGI Nokapaka - Satunggale Kurniawan; Rahman, Muhammad Afifi; Mendiron Yigibalom (Journal on Pustaka Cendekia Informatika, 2024)
The success of the teaching and learning process is largely determined by a teacher who transfers knowledge through the learning process, in this case learning strategies are important in the learning process. Many lessons in class are carried out by teachers, lessons that are often used in the learning process include: lecture learning, question and answer learning, discussion learning, assignment learning, demonstration learning, field trip learning, group work (inquiry), learning role playing, dialogue learning, argumentative learning, and story telling. Based on the considerations above, it is necessary to develop a learning method that is able to involve student participation as a whole so that teaching and learning activities are not only dominated by certain students. In addition, through choosing this learning method, it is hoped that the source of information that students receive will not only come from the teacher but can also increase student participation and activeness in studying and reviewing existing knowledge, especially English subjects. Based on the background of the problem above, the title of this classroom action research was formulated as follows: "Improving learning outcomes for speaking English fluently through learning with puzzle games as a medium for fifth grade students at SD YPPGI NOKAPAKA for the 2023/2024 academic year." The results of this research are: How do students' activities in learning using puzzle games media improve learning outcomes in English speaking among fifth grade students at SD YPPGI NOKAPAKA and can learning using puzzle games media improve the understanding of fifth grade students at YPPGI NOKAPAKA Elementary School about providing information in language? English, This research uses a qualitative approach, namely a form of reflective study by the perpetrators of actions carried out to increase rational stability and also uses classroom action research, namely their actions in carrying out assignments and Puzzle Games are a form of game that challenges creativity and memory. students are more in-depth due to the emergence of motivation to always try to solve problems, but it is still fun because it can be repeated.